A conceptual approach for developing an ergonomic intervention for preventing Work‐related Musculoskeletal Disorders (WMSD) amongst workforce at power plants - Sivadass Thiruchelvam,; Nurainaa Kabilmiharbi,; Fevilia Nurnadia Adria Syaifoel,; Zubaidi Faiesal Mohamad Rafaai,; Azrul Ghazali,; Kamal Nasharuddin Mustapha,; Rahsidi Sabri Muda, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Work at fossil-fuelled power plant is physically strenuous and could expose workers to Work-related Musculoskeletal Disorder (WMSD) such as Carpal Tunnel Syndrome (CTS), low-back pain (LBP), or shoulder tendonitis. WMSDs are considered as a leading factor in disabilities and absenteeism, reduced production, and increased costs. WMSDs in the workplace have been studied extensively and it is a common notion that the work itself is a major cause of MSDs. Work environment contributed to these types of disorders and are made worse by the working conditions or workplace risk factors. All those mentioned common occupational injuries are related with the ergonomic field of study. By implementing appropriate ergonomic interventions, the above-mentioned work-related injuries and resulting disability is potentially preventable. The major workforce in these plants are either associated with handling of machineries or serving as control room operators. Hence, this category of manpower is subjected to physical stress and workplace injuries if there is no form of ergonomic interventions. Previous studies have shown that common tasks performed by workers in the electric power industry often involve the use of a manual tool and revealed that less than 1% of the general population has sufficient strength to manually perform the task resulting in decreased productivity and worker injury. Departing from the aforementioned need, this study embarks to assess exposure to risk factors for WMSDs and to provide a basis for ergonomic intervention at the workplace. Therefore, by focusing on health and safety matter of workers at our power plants, we are actually applying a form of business risk management (BRM) to consider possible impacts of related foreseeable significant risks on any electricity utilities performance. It is envisaged that this study could identify the ergonomics interventions which will reduce staff medical bills, compensation, and lost time injury from MSDs.